Corporate Immunizations Scheduleasa Technology for Managing of the Workers Health - I. V. Fel'dblium (Эпидемиология и вакцинопрофилактика)
Relevance. In modern conditions, special attention is paid to preserving the health and quality of life of the working population through vaccination. The role of corporate medicine in the organization and implementation of a risk-based approach to the immunization of employees in enterprises and institutions is actively discussed. The aim of this study was to discuss the methodological and basic arrangements for the development and implementation of a new technology at an enterprise using vaccination - a corporate immunizations schedule. Materials and methods. The scientific work was carried out on the basis of generalization of our own experience and the experience of some regions of the Russian Federation on the formation and implementation of corporate immunizations schedules in industrial enterprises and in higher educational institutions. Results. The substantiation of the feasibility of introducing corporate immunizations schedules at enterprises and institutions is given, tasks, legal bases, an up-to-datelist of infections to be included in the corporate immunization schedules, conditions for its successful implementation and development prospects are presented. Conclusions. The corporate immunization schedules should be considered as one of the mechanisms for providing the working population with immunobiological drugs during the transition period (before the inclusion of actual infections in the National immunization schedule), actively discussed today in the pages of domestic literature.